Evaluation of Early and Late Complications of Pediatric Liver Transplantation with Multi-slice Computed Tomography: A High-Volume Transplant Single-Center Study - Öztürk, Mehmet; Dağ, Nurullah; Sığırcı, Ahmet; Yılmaz, Sezai (Turkish Journal of Gastroenterology, 2021)
Background: To present abdominal multi-slice computed tomography (MSCT) results following transplantation in pediatric patientswith a liver transplantation (LT), and to create awareness of early (<3 months) and late (>3 months) complications that may occur.Methods: This retrospective study included 119 children with an LT performed in our hospital from 2014 to 2017. The descriptive statisticsrelating to patients’ age, gender, transplantation indications, transplantation technique, and MSCT findings were calculated,and are presented as numbers and percentages. The complications were divided into 4 groups: vascular, biliary, parenchymal, andextraparenchymal.Results: The LT procedures were performed with organs from living donors for 83 patients, and from deceased donors for 36 patients.Hepatic artery and portal vein complications were mostly seen in the early period (n = 18), and hepatic vein complications were alsoobserved in the late period (n = 6). The most commonly encountered biliary complications were stenosis/stricture (n = 13) and bile leak/bilioma (n = 9). Stenosis/stricture frequently occurred in the late period. The most common parenchymal complications were ischemicinfarct (n = 8) in the early period, and abscess (n = 4) and recurrent hepatoblastoma (n = 2) in the late period. Hematoma (n = 7),intestinal perforation (n = 3), and focal spleen infarct (n = 3) were among the most commonly observed extraparenchymal abdominalcomplications.Conclusion: The complications occurring after pediatric LT varied according to the time after surgery and the transplantation techniqueused. Using MSCT, different abdominal complications can be assessed simultaneously, greatly contributing to diagnosis and treatment.